Decapod crustaceans on dead coral from reef areas on the coast of Bahia, Brazil - Santos,Patricia Souza (2012)
The decapod crustaceans inhabiting dead portions of the fire-coral Millepora alcicornis Linnaeus, 1758 and coral rubble were surveyed in six reef areas on the coast of the state of Bahia, Brazil, in 2011. A total of 453 specimens belonging to 39 species in the infraorders Stenopodidea (family Spongicolidae), Caridea (families Palaemonidae, Alpheidae, Hippolytidae, and Processidae), Axiidea (family Callianassidae), Gebiidea (family Upogebiidae), Anomura (family Porcellanidae), and Brachyura (families Majidae, Pilumnidae, Domeciidae, Panopeidae, and Grapsidae) were collected. Members of the families Alpheidae and Porcellanidae were prominent, with 14 and 9 species, respectively. Of the species collected, the alpheid shrimp Alpheus peasei (Armstrong, 1940) is recorded for the first time in the southwestern Atlantic. Microprosthema semilaeve (von Martens, 1872), Corallianassa hartmeyeri Schmitt, 1935, and Petrolisthes marginatu Stimpson, 1859 also had their known geographic ranges extended along the western Atlantic. Alpheus nuttingi (Schmitt, 1924), Synalpheus scaphoceris Coutière, 1910, and Pachycheles riisei (Stimpson, 1858) are new records for Bahia.